Mechanical Properties of Advanced Multifunctional Coatings - Xu, Rong-Guang (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Advanced multifunctional coatings have made great unexpected advances in synthesis, characterization and properties, and they are also used in a variety of different fields. The mechanical properties of multifunctional coatings play a vital role in their interaction with external forces and environmental factors. Therefore, it is necessary to fully study the mechanical properties of advanced multifunctional coatings. After the launch of the Special Issue, thirteen papers have been collected and published. These original research articles cover not only the relevant research of advanced multifunctional coatings but also the interesting mechanical behaviour of surfaces and interfaces. We feel that the Special Issue provides a forum to share current research results and to promote further research into the mechanical behaviour of advanced multifunctional coatings.